The effect of active recovery, cold water immersion and passive recovery on subsequent knee extension and flexion strength - Barbora Strejcová; Renata Konopková (Palacky University, 2012)
BACKGROUND: Recovery is an important aspect of every physical activity. Many athletes train hard without giving their body time to recover which can lead to overreaching, burnout or poor performance. Currently cold-water immersion recovery and active recovery have emerged as some of the most popular interventions enabling faster recovery. OBJECTIVE: To assess the effect of three kinds of recovery (active recovery, cold water immersion, passive recovery) on medium-term knee strength in the extension and flexion. METHODS: Fourteen athletes at the age of 26.6 ± 4.4 years performed, in a random cross-over design, 3 sessions with 3 repeated medium-term isokinetic tests. The effect of active recovery, passive rest and cold water immersion were assessed by 3 × 3 (time × recovery) repeated-measure ANOVA, respectively. The dependent variables were - peak torque, total work and average power. RESULTS: We found significantly lower absolute differences between the first and third trial in knee extension for peak torque after the active recovery (↑ 0.9 N × m) than after the cold water immersion (↓ 14.6 N × m) or the passive recovery (↓ 13.9 N × m). The decrease of the average power was significantly lower differences after the active recovery (↓ 5 W) than after the cold water immersion (↓ 23.7 W) or passive recovery (↓ 25.9 W). The changes in total work were not significant. We did not found any changes in the isokinetic strength for the knee flexors after different kinds of recovery. Maximal heart rate (HRmax) was significantly higher during the active recovery than during the cold water immersion and the passive recovery (173 ± 14, 166 ± 14 and 167 ± 14 rpm). We have found significant differences in the average heart rates (HRavg) during active recovery, cold water immersion and passive recovery (124 ± 8, 97 ± 9 and 107 ± 12 rpm). CONCLUSION: We found the positive effect of the active recovery on the subsequent medium-term performance for knee extension. That was the only method which showed lower decrease of knee strength in extension in comparison with passive recovery and cold water immersion. We have found the significant differences of heart rate which was recovery dependent.